Evaluation of Hepatoprotective Potential of Bougainvillea spectabilis Extracts against CCl4-Induced Hepatotoxicity - Das, Prabhat Kumar; Vaghela, Jai Singh (Indian Journal of Pharmaceutical Education and Research, 2024)
Background Injuries and fatalities caused by liver disease are among the highest in the globe. Every year, more than one million people lose their lives due to chronic hepatitis, which affects an estimated 500 million people worldwide. In order to create liver disease treatments that can successfully cure or slow the illness’s progression without side effects, new approaches are needed. Objectives The present study’s aim is to examine and confirm the buffering properties of Bougainvillea spectabilis extracts of ethanolic and aqueous against rat hepatic damage caused by CCl4. Materials and Methods The mice were grouped into several groups. To induce acute and massive hepatopathy, CCl4 was injected intraperitoneally in a 1:1 ratio with olive oil at a dosage of 2 mL/kg. The toxic control group showed significant weight loss after the intoxication, as revealed by evaluation of biochemical parameters. The hepatoprotective effect was investigated by measuring body weight, serum liver enzymes such as AST, ALT, ALP, SGPT, SGOT, Total protein and albumin. Liver histopathology was then used to evaluate the hepatic architecture, every alignment and inflammatory cells. Results All of the rats treated with carbon tetrachloride had significantly elevated protective markers and the rats given B. spectabilis extracts i.e. ethanolic and aqueous made a full recovery, returning to nearly normal levels. Histological examination corroborated these results, which indicate that B. spectabilis protected the cellular architecture of Carbon Tetrachloride-damaged liver cells and the hepatic membrane’s structural integrity. During comparison to the aqueous group, the rats administered with the ethanolic extract showed promising outcomes that were on par with those of a conventional polyherbal medicine. Conclusion Thus, ethanolic extract of the plant B. spectabilis may have a protective role against CCl4-induced hepatopathy, according to the statistically significant results of our investigation.
Keywords: Bougainvillea spectabilis; Carbon Tetrachloride; Hepatopathy; SGPT; SGOT